Mid‐regional pro‐atrial natriuretic peptide independently predicts short‐term mortality in COVID‐19. (10th March 2021) - Kaufmann, Christoph C.; Ahmed, Amro; Kassem, Mona; Freynhofer, Matthias K.; Jäger, Bernhard; Aicher, Gabriele; Equiluz‐Bruck, Susanne; Spiel, Alexander O.; Funk, Georg‐Christian; Gschwantler, Michael; Fasching, Peter; Wojta, Johann; et al.
Abstract: Background: Mid‐regional pro‐atrial natriuretic peptide (MR‐proANP) is a strong prognostic marker in several inflammatory, respiratory and cardiovascular conditions, but has not been studied in COVID‐19 yet. Methods: This prospective, observational study of patients with COVID‐19 infection was conducted from 6 June to 26 November 2020 in different wards of a tertiary hospital. MR‐proANP, N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) and high‐sensitive cardiac troponin I levels on admission were collected and tested for their association with disease severity and 28‐day mortality. Results: A total of 213 eligible patients with COVID‐19 were included in the final analyses of whom 13.2% (n = 28) died within 28 days. Median levels of MR‐proANP at admission were significantly higher in nonsurvivors (307 pmol/L IQR, [161 ‐ 532] vs 75 pmol/L [IQR, 43 ‐ 153], P < .001) compared to survivors and increased with disease severity and level of hypoxaemia. The area under the ROC curve for MR‐proANP predicting 28‐day mortality was 0.832 (95% CI 0.753 ‐ 0.912, P < .001). An optimal cut‐off point of 160 pmol/L yielded a sensitivity of 82.1% and a specificity of 76.2%. MR‐proANP was a significant predictor of 28‐day mortality independent of clinical confounders, comorbidities and established prognostic markers of COVID‐19 (HR 2.77, 95% CI 1.21 ‐ 6.37; P = .016), while NT‐proBNP failed to independently predict 28‐day mortality and had a numerically lower AUC compared to MR‐proANP. Conclusion: Higher levels of MR‐proANP at admission are associated with disease severity of COVID‐19 and act as a powerful and independent prognostic marker of 28‐day mortality.